Fungal and mycotoxins contamination in corn silage: Monitoring risk before and after fermentation - Keller, L. A. M. (2013)
Silage is a widespread practice to preserve forage. Poor storage conditions can lead to mold contamination and mycotoxin production. The aim of this study was to establish the occurrence of toxigenic fungal species and to determine aflatoxins (AFs), ochratoxin A (OTA), fumonisin B1 (FB1) and deoxinivalenol (DON) in corn silage intended for bovines before and after fermentation in farms located in São Paulo and Rio de Janeiro States, Brazil. Fungal counts were done by surface-spread method. Toxigenic ability of isolates was evaluated in vitro. AFs natural contamination was determined by TLC and HPLC. Total fungal counts were generally high. Aspergillus flavus, Penicillium citrinum, and Fusarium verticillioides were the prevalent species. Toxigenic strains were isolated. Aflatoxin levels differed (P < 0.0001) from 2 to 45 μg g-1 and from 2 to 100 μg g-1 in pre and post-fermentation samples, respectively. Ochratoxin A, FB1 and DON levels found in pre-fermentation samples were higher than in post-fermentation (P < 0.0001). Mycotoxins and toxigenic fungi were present before and after fermentation in corn silage intended for bovines in Brazil. Aflatoxin B1 (AFB1) increased during storage whereas OTA, FB1 and DON decreased. Determination of mycotoxin levels and their occurrence in corn silage are important to provide information so that the assessments of risk for animal feed and livestock environment could be made.